Dynamics of water waves over fringing coral reefs - Yao, Yu (2012)
This thesis reported a comprehensive study of the wave dynamics over fringing coral reefs, including laboratory experiments, numerical modeling and theoretical analyses. Two main sets of experiments were performed in a wave flume to measure the breaking-wave characteristics over an idealized fringing reef and to study the wave-induced setups and flows on a horizontal reef flat with and without an idealized ridge, respectively. A numerical study based on Boussinesq-type equations was presented, the numerical model was calibrated by our measurements and applied to investigate the cross-shore wave transformation and setup. Two analytical models were proposed to reproduce the wave setup in the absence/presence of the ridge: a kinematic model based on mass balance and some hydraulics, and a dynamic model based on cross-shore momentum balance and the radiation stress concept. Both models were validated against the experiments. The dynamic model was also applied to some field data.